مستوى فاعلية الذات لدى طلاب الجامعة العربية المفتوحة وعلاقته بمستوى دافعيتهم نحو التعلم - العشيري، هشام أحمد يوسف (جامعة الإسكندرية - كلية رياض الأطفال, 2015)
هدفت الدراسة إلى قياس العلاقة بين مستوى فاعلية الذات، ومستوى دافعية التعلم لدى طلاب برنامج بكالوريوس تقنية المعلومات وبكالوريوس إدارة الأعمال بالجامعة العربية المفتوحة في مملكة البحرين. وللإجابة عن أسئلة الدراسة وتحقيق أهدافها استعان الباحث بالمنهج الوصفي التحليلي لمناسبته لطبيعة الدراسة وعينتها. وخلصت الدراسة لعدة نتائج أهمها تمتع أفراد العينة بمستوى متوسط من فاعلية الذات، وكذلك مستوى متوسط من دافعية التعلم، ووجود علاقة دالة إحصائيا بين مستوى فاعلية الذات ومستوى دافعية التعلم لدى طلاب الجامعة العربية المفتوحة في مملكة البحرين.
The study aimed to measure the relationship between the level of self-effectiveness and level of motivation toward learning for the IT and computer programme students in the college of business Administration at Arab Open University – Kingdom of Bahrain branch. To achieve this aim, the researcher followed the descriptive analytical approach due to its suitability to the nature of the study in terms of research questions and sample. The results of the study revealed that IT and Computer programme students at Arab Open University enjoy a moderate level of self-effectiveness and motivation to learning. The findings also showed there is a significant relationship between self-effectiveness and level of motivation on the part of the Open Arab University students in this regard.
Keywords: الاستراتيجيات التعليمية -- طلبة الجامعات -- الدافعية التعليمية -- التحصيل الدراسي